The Common Theme of the Parables of Ashab-ı Kahf, Khidr and Zulqarnayn: Mercy - Ertuğrul, Muzaffer (Fırat University, 2022)
The three parables told in the chapter of al-Kahf are among the most interesting parables of the Qur'an. The first of these parables is the story of Ashab-i Kahf, in which the young people who took shelter in the cave are narrated; the second is the story of Khidr, in which the work of Khidr, is told, and the third is the story of Zul-qarnain, in which the adventure of Zul-qarnain, is narrated. These stories seem unrelated to each other in terms of their events, persons, places, times. Narrating these stories that seem unrelated to each other in the same time could not be made sense of by some westerners. For example, psychologist Carl Gustav Jung considered the narration of these unrelated stories in the same surah as an anachronism. However, although these stories are independent of each other in terms of events, times, places, and persons, they are united in a common theme in terms of the divine message they want to convey to humanity. This common theme is the concept of mercy. Through these parables, Allah conveys the message that divine mercy can reach his servants for many reasons. These reasons can sometimes be a place, sometimes a servant, sometimes an object.

Kehf sûresinde anlatılan üç kıssa Kur’ân’ın en ilginç kıssalarındandır. Bunlardan birincisi mağaraya sığınan gençlerin anlatıldığı Ashâb-ı Kehf kıssası; ikincisi Mûsâ Peygamber’in yol arkadaşı Hızır’ın işlerinin anlatıldığı Hızır kıssası ve üçüncüsü Zülkarneyn’in serüveninin anlatıldığı Zülkarneyn kıssasıdır. Bu kıssalar olayları, kahramanları, mekânları, zamanları bakımından birbiriyle alakasızdır. Birbiriyle alakasız olan bu kıssaların aynı sûrede anlatılması bazı batılılar tarafından anlamlandırılamamaktadır. Meselâ psikolog Carl Gustav Jung birbiriyle bağlantısız bu üç kıssanın aynı sûrede anlatılmasını Hz. Peygamber açısından bir anakronizm olarak değerlendirmektedir. Hâlbuki bu üç kıssa olayları, zamanları, mekânları ve eşhâsı cihetinden birbirinden kopuk olsa da insanlığa vermek istediği ilâhî mesaj bakımından müşterek bir temada birleşmektedir. Bu müşterek tema rahmet kavramıdır. Allah bu kıssalar üzerinden rahmetinin kullarına pek çok vesîleyle ulaşabileceği mesajını vermektedir. Makalede üç kıssanın ortak teması olan rahmet kavramı üzerinde durulmuş ve kıssalarda anlatılan olaylarla Allah’ın rahmeti arasındaki bağlantıya işaret edilmiştir. Bu yapılırken Kur’ânî bir üslûb tercih edilerek Allah’ın gizli bıraktığı mekân, zaman, şahıslar üzerinde gereksiz yere durulmamıştır.
Ashâb-ı Kehf, Hızır Ve Zülkarneyn Kıssalarının Ortak Teması: Rahmet
Keywords: Religious Studies; Din Araştırmaları